The role of public-private cooperation in the management of estuarine fisheries: Learning from the Kerala model of co-management - K.T .THOMSON (Paper presented at the 11th biennial conference, of the International Association for the Study of Common Property (IASCP), Bali Indonesia June 19 - 23, 2006, 2006)
The objective of this paper is to present the history and present structure of such a co operative arrangement in the management of fisheries in Cochin estuary. We shall highlight how the local state (Grama Panchayath) and communities together share the responsibility to allocate fisheries to various fishing groups and private entrepreneurs in the northern side of the Cochin estuary. The study also focuses on the role of various traditional management institutions to ensure resource sustainability and equitabledistribution. The paper is organized as follows. After sketching the ecological/environmental setting of the study area in section 1, the paper narrates the history of management in section 2. Section 3 describes how local Panchayath took over fisheries management and explains how it manages fisheries with the help of private entrepreneurs and local fishing communities. This section also narrates the benefits accrued to various parties in joint management and the various formal (state and local state level) and informal (non state) rules and regulations that govern various organizing practices in the study area. Section 4 explains the nature of conflicts in the area with respect to the sharing of resources and presents how these are resolved and section 5 discusses the limitations of this local cooperative arrangement. A conclusionfollows.